Peran Komunikasi Pemasaran dalam Membangun Brand Image guna Mempengaruhi Keputusan Pembelian Konsumen di Brighton Real Estate Indonesia Cabang Surabaya - Efrizar Sunni; Dicky Darma Putranto; Is Fadhillah (Universitas Nusantara PGRI Kediri, 2025)
This study examines the strategies implemented by Brighton Real Estate Indonesia in forming the company's brand image. This study applies a qualitative descriptive method to describe facts and data related to marketing communication strategies, which are analyzed based on the theory of marketing mix, persuasive communication, and integrated marketing communication. Data were obtained from interviews, direct observation, and document collection. The main informants were agents, property owners and buyers. Meanwhile, the data validity test was carried out through triangulation. Based on the results of the study, the marketing strategy implemented by Brighton Real Estate Indonesia has integrated most of the elements in the marketing mix. The company's focus is seen in providing quality products, competitive price offers, aggressive promotions, strategic location selection, and communication approaches in the form of advertising and direct education to potential consumers. This study also found that the marketing communication approach used by Brighton also had an impact on increasing the company's brand image, so it can be concluded that Brighton Real Estate Indonesia has implemented an effective marketing communication strategy that has an impact on the company's brand image so that this influences consumer decisions to make buying and selling transactions at Brighton Real Estate Indonesia.